ΔΥΟ ΝΕΟ - ΑΤΤΙΚΑ ΗΜΙΕΡΓΑ ΣΤΟ ΕΘΝΙΚΟ ΜΟΥΣΕΙΟ - ΠΑΛΑΓΓΙΑ ΟΛΓΑ (Μνήμων, 1972)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–>Δεν παρατίθεται περίληψη<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>